Therapeutic effect of anti-feline TNF-alpha monoclonal antibody for feline infectious peritonitis. (February 2016) - Doki, Tomoyoshi; Takano, Tomomi; Kawagoe, Kohei; Kito, Akihiko; Hohdatsu, Tsutomu
Abstract: Feline infectious peritonitis virus (FIPV) replication in macrophages/monocytes induced tumor necrosis factor (TNF)-alpha production, and that the TNF-alpha produced was involved in aggravating the pathology of FIP. We previously reported the preparation of a feline TNF-alpha (fTNF-alpha)-neutralizing mouse monoclonal antibody (anti-fTNF-alpha mAb). This anti-fTNF-alpha mAb 2–4 was confirmed to inhibit the following fTNF-alpha-induced conditions in vitro. In the present study, we investigated whether mAb 2–4 improved the FIP symptoms and survival rate of experimentally FIPV-inoculated SPF cats. Progression to FIP was prevented in 2 out of 3 cats treated with mAb 2–4, whereas all 3 cats developed FIP in the placebo control group. Plasma alpha1-glycoprotein and vascular endothelial growth factor levels were improved by the administration of mAb 2–4, and the peripheral lymphocyte count also recovered. These results strongly suggested that the anti-fTNF-alpha antibody is effective for the treatment of FIP. Highlights: Feline infectious peritonitis (FIP) is a coronavirus-induced fatal disease in cats. We investigated therapeutic effect of anti-fTNF-α mAb for experimental FIP infection. Anti-fTNF-α mAb improved the FIP symptoms and survival rate in 2 of 3 cats. Anti-fTNF-α mAb improved plasma AGP and VEGF level and lymphopenia. The results suggested the anti-fTNF-α mAb may be effective for the treatment of FIP.